The animated pocket dictionary of infectious diseases - Focus Medica ([Singapore] : Focus Medica, 2011)
The FOCUS Animated Pocket Dictionary of Infectious diseases, the first ever animated dictionary in the subject, fill that void quite effectively. A must-have resource for physicians and students who would greatly benefit from this module, it covers terms and definitions. All the definitions have been described with breathtaking, state of the art 3D animations.
A-Z.
System requirements: DVD-ROM drive; OS Windows 98/ME/XP/Windows vista, CPU PIII/1Ghz; RAM 128Mb preferred.
Keywords: Communicable diseases; Dictionary; Electronic books